2001
DOI: 10.1002/jrs.760
|View full text |Cite
|
Sign up to set email alerts
|

A SERS probe of adenyl residues available for intermolecular interactions. Part I—adenyl ‘fingerprint’

Abstract: This work validated a SERS probe able to compare adenyl reactivity in DNA and RNA. A Creighton silver colloid including adenine (A) [or 2 -deoxyadenosine 5 -phosphate (pdA)] from 2 × 10 −3 to 2 × 10 −8 M is stabilized in the absence or presence of chloride. Concentration-dependent SER spectral profiles reveal how A may interact with (Ag) n + sites. At concentration ≥2 × 10 −5 M adsorption of (A) n clusters prevents the colloid from undergoing salt effects. Adsorption via N1/N3 is allowed whereas C6NH 2 is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(92 citation statements)
references
References 54 publications
(21 reference statements)
6
85
1
Order By: Relevance
“…Since the responses of adenine and pdA (5 0 -monophosphate deoxy adenosine) were dramatically greater than those of the other bases and mononucleotides, we concluded that the reactivity of adenine and adenyl residues with the silver electropositive sites is much greater than that of the other nucleic bases or base residues. 41 The similar SER spectral profile obtained for adenine, pA (5 0 -monophosphate adenosine), pdA, dA tracts, and A in r and d-hairpins in the 2 Â 10 À6 to 2 Â 10 À8 M concentration (c) ranges prove that adenine and adenyl residues bind similarly to [Ag] þ n . [41][42][43] Only the relative spectral intensities varied, which are representative of different amounts of A loaded on [Ag] þ n (A-loading).…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Since the responses of adenine and pdA (5 0 -monophosphate deoxy adenosine) were dramatically greater than those of the other bases and mononucleotides, we concluded that the reactivity of adenine and adenyl residues with the silver electropositive sites is much greater than that of the other nucleic bases or base residues. 41 The similar SER spectral profile obtained for adenine, pA (5 0 -monophosphate adenosine), pdA, dA tracts, and A in r and d-hairpins in the 2 Â 10 À6 to 2 Â 10 À8 M concentration (c) ranges prove that adenine and adenyl residues bind similarly to [Ag] þ n . [41][42][43] Only the relative spectral intensities varied, which are representative of different amounts of A loaded on [Ag] þ n (A-loading).…”
Section: Introductionmentioning
confidence: 52%
“…41 The similar SER spectral profile obtained for adenine, pA (5 0 -monophosphate adenosine), pdA, dA tracts, and A in r and d-hairpins in the 2 Â 10 À6 to 2 Â 10 À8 M concentration (c) ranges prove that adenine and adenyl residues bind similarly to [Ag] þ n . [41][42][43] Only the relative spectral intensities varied, which are representative of different amounts of A loaded on [Ag] þ n (A-loading). At a given concentration, the greater the load the more A is assumed to be reactive.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations